Performance Analysis of IoT Adaption Layer Protocol - ., Nikshepa; Pai, Vasudeva; Pai, Karthik; Kumar K Shenoy, Udaya (International Journal of Engineering and Technology, 2018)
The network communication in the real world has a significant consumption of energy and the processing power involved.Â  The components used for the network communication like the protocol and the other mechanisms used consumes a large amount of energy. As a result the low power networks like WSN and the IoT motes face a lot of difficulties for the processing. As a solution to this IETF group called for a new protocol that utilized a low energy in Low power and a Lossy networks. IPv6 over Low Power Wireless Personal Area Networks abbreviated as 6LowPan protocol was designed for the working in the low power networks.In the paper, we have a detailed analysis carried out on the performance of the 6LowPan protocol with different number of nodes. The performance are evaluated for number of parameters like throughput, latency, power etcÂ